Pemberdayaan Masyarakat melalui Pembangunan Bidang Pendidikan Nonformal - Supsiloani Supsiloani (Universitas Negeri Medan, 2019)
This article examines non-formal education which is not less important than formal education from all levels of education. Non-formal education is also expected to meet the needs of the population in terms of knowledge, information and technology. All of that becomes very necessary to improve the quality and standard of living of the people. Non-formal education is carried out to obtain relevant skills for the provision of daily living. The skills obtained, make the community have an independent mental attitude, renewal and development for the progress and development of the country. Independence in the fulfillment of everyday life, which is from expertise acquired, to be able and can be enjoyed, comes from one's own business. Likewise the results obtained, can be exchanged with other parties. Thus the ultimate goal is to empower the community, enable and build the ability to advance towards a better life on an ongoing basis.